A STUDY OF DIATOMS (BACILLARIOPHYTA) IN HOOR-AL-AZIM WETLAND, SOUTH-WEST IRAN, AND THEIR SEASONAL CHANGES - Dezhman, M.; Dehghan, S.; M Hassan, F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to identify the planktonic diatoms and their seasonal change in Hoor-AL-Azim wetlands, Iran. Diatoms are important algal groups in different aquatic ecosystem and considered as bioindicators for water quality and environmental health. Hoor-AL-Azim or Hoor-al-Hawizeh is one of the most extensive and ecologically important wetlands in the Middle East which is shared between Iran (south-west) and Iraq(south). A major part of the wetland area was exposed to drying completely or partially during last few decades due to two Country politics. The samples were taken on a monthly basis from four stations for year from January to end of December, for  identification and seasonal changes of Diatoms (Bacillariophyta). In this study, totally  69 taxa belonging to 28 different genera were identified of which Nitzschia genus had the highest species diversity (13 species) and followed by Navicula genus (10 species) while the highest species diversity observed in autumn. The average density ranged from 4818 cells/ liter  to 58625 cells /liter in spring and winter, respectively.